Repeated stimulation of CRF receptors in the BNST of rats selectively induces social but not panic-like anxiety - Lee, Younglim (2008)
Increased extra-hypothalamic corticotrophin releasing factor (CRF) neurotransmission has been suggested as one putative factor in the pathophysiology of anxiety disorders. We have previously reported that administering repeated sub-anxiogenic doses (termed “priming”) of the CRF receptor agonist urocortin 1 (Ucn1) into the basolateral amygdala (BLA) of rats elicited long-lasting behavioral changes in social interaction (SI) and elevated plus-maze (EPM) tests of anxiety. Although substantial similarity exists, the bed nucleus of the stria terminals (BNST) and the amygdala are thought to play distinct roles in anxiety responses. Rats primed with Ucn1 in the BLA not only demonstrated increased anxiety-like behaviors, but also physiological sensitivity to intravenous sodium lactate infusions, which is seen in subjects with panic or post-traumatic stress disorders, but not social or generalized anxiety disorders. In the present study, we tested if similar priming with sub-anxiogenic doses of Ucn1 in the BNST of rats will induce either chronic anxiety or sensitivity to sodium lactate. After determining the dose of Ucn1 that is sub-anxiogenic when injected into the BNST, repeated intra-BNST injections of this sub-anxiogenic dose of Ucn1 (6 fmoles/100 nl) elicited persistent (present even after 4 weeks) anxiety-like responses in the SI but not EPM test. Prior local injection of a CRF receptor antagonist, astressin, into the BNST blocked this effect. Unlike Ucn1 priming in the BLA, rats primed in the BNST showed no cardiovascular changes following lactate infusion. Thus, BNST priming appears to selectively model the pathophysiology of subjects with anxiety syndromes like social anxiety that are not lactate sensitive.